(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Surrogate commercials are a distinct type of marketing in which the actual product, which may be outlawed or restricted by legislation, cannot be explicitly featured or its traits and features depicted as they are. Instead, surrogate adverts aim to pique the viewer's curiosity and communicate a message without openly exposing the product. It's crucial to emphasize that surrogacy marketing isn't always harmful or unlawful. Surrogate advertising has been effective in enticing clients, particularly the younger generation, who have been heavily enticed into purchasing and ingesting forbidden items. In this perspective, the current study examines the influence of surrogate advertising on generation Z. The current study found that the majority of Generation Z is aware of surrogate marketing and their influence on tobacco smoking. They believe that the appearance of well-known celebrities in such advertising enhances tobacco usage while also creating a good brand image for the corporations that produce and promote the products.